Pierwsza msza św. w języku polskim w Koszalinie. (Gdańsk : [s.n.], 1946)
Afisz inf. o mszy 13.10.1946 r.
Keywords: Koszalin (Polska) -- 1945-1970 -- druki ulotne; Koszalin (Polska) -- 1945-1970 -- życie religijne